Effects of Self-Regulated Learning on Student’s Reading Literacy: Evidence From Shanghai - Qi, Xiang (Frontiers in Psychology, 2021)
Many empirical studies have been conducted to investigate self-regulated learning (SRL) in the Western countries. Less well investigated is the SRL in the Chinese Mainland students and how it affects their academic achievement. On the basis of PISA 2009, this paper is aimed at exploring SRL of 15-year-old Shanghai students, as measured by cognitive strategy (elaboration; memorization), metacognition (metacognition in understanding and remembering; metacognition in summarizing; control strategy), and motivational belief (enjoyment of reading). In the aspect of SRL’ nature, results reveal that 15-year-old students in Shanghai use elaboration strategy frequently while use memorization strategy seldom, and that they have high metacognition in understanding, remembering, summarizing but low control strategy, and that their enjoyment of reading is relatively high. In the aspect of SRL’s consequence for reading literacy, findings from multilevel linear regression corroborate previous evidence from the Western countries about the effect of SRL on academic achievement. Specifically, elaboration strategy, metacognition in understanding and remembering, metacognition in summarizing, control strategy, and enjoyment of reading are conductive to students’ reading literacy, while memorization strategy exerts a significantly negative effect on reading literacy. The findings could be useful for helping us to gain a better understanding of Shanghai students’ SRL.